On the presence of Ocnus planci Brandt, 1935 (Echinodermata: Dendrochirotida: Cucumariidae) in the Mostaganem region (Western Algerian coast) - Mezali, Karim; Zerroual, Hanane; Lebouazda, Zineb; Khodja, Ihcene (Zootaxa, 2024)
In Algeria, few studies have been carried on the Holothuriodea especially the family Cucumariidae Ludwig, 1894. A specimen was caught as bycatch from a commercial benthic trawler on the Mostaganem coast (northwest of Algeria). Based on a detailed study of the morphological, anatomical and endoskeletal characters, this specimen is confirmed to be Ocnus planci (Brandt, 1835). We report it herein as the first observation from the Algerian west coast. This species has been recorded several times in the Mediterranean sea. It is characterised by a calcareous ring, whose radial plates are longer than the interradial plates, the presence of buttons and perforated button plates of different sizes in the body wall, as well as various shapes of rosettes, baskets and nodules with small perforations.